Analisis Permasalahan Belajar Matematika Siswa Kelas VII SMP Asrol Ulum: Hasil Penelitian Permasalahan Belajar Matematika - Firdaus, Moh Ghufron; Rozie, Fachrur (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to identify and analyze mathematics learning problems faced by class VII students at Asrol Ulum Middle School, as well as offering relevant solutions based on a review of references and previous research results. The research method uses a qualitative descriptive approach, with data collected through interviews and distributing questionnaires to students. The research results show that factors such as geographical location, interest and motivation to learn, understanding of basic concepts, teacher learning strategies, family support, and learning facilities and infrastructure influence mathematics learning. The proposed solutions include teacher training and development, project-based learning, differentiated learning strategies, good communication between schools and parents, and utilization of local resources. This research provides an in-depth understanding of mathematics learning problems and solutions that can be applied to improve the quality of education at Asrol Ulum Middle School.